Boron deficiency in wheat: A review - Rerkasem B. (2014)
Although cereals are generally considered to be insensitive to boron (B) deficiency, incidences of B deficiency have been reported from many of the world's wheat growing countries since the 1960s. The most extensive region of B deficiency in wheat so far reported is the adjoining area of eastern Nepal, northeastern India and northwestern Bangladesh, through to southwestern China. Wheat is more prone to B deficiency than rice and maize, and some dicotyledons including soybean and mungbean. Although it has been reported to adversely affect many processes of wheat growth and development, B deficiency depresses commercial wheat yield primarily through grain set failure, which is in turn caused by male sterility. The function of wheat anthers has been found to be impaired when their B concentration per unit dry weight was 10 times that found limiting for vegetative growth. Wheat genotypes vary greatly in their adaptation to low B soils. Boron efficient genotypes may grow and yield normally on low B soils in which inefficient genotypes are so adversely affected by B deficiency that they set no grain at all. International germplasm from the International Maize and Wheat Improvement Centre (CIMMYT) on which most developing countries depend for their new wheat cultivars is largely B inefficient. Wheat production in the world's growing areas on low B soils should greatly benefit from increasing B efficiency in internationally important germplasm. This should be highly feasible as a few B efficient advanced breeding lines have already been identified and B efficiency is under the control of major genes. © 2004 Elsevier B.V. All rights reserved.